Effectiveness of stenting and subsequent re‐implantation of disconnected pulmonary artery to restore the pulmonary hemodynamics - Saad Khoshhal; Mansour Al‐Mutairi; Mohamed Morsy; Nasser Kreary; Abdulhameed Alnajjar; Hany Abo‐Haded (Wiley, 2021)
ABSTRACT Introduction Early intervention in patients with congenitally disconnected pulmonary artery improves long‐term outcome. Case presentation We present 3 cases of isolated disconnected pulmonary artery in the absence of associated structural heart disease during a period of 3 years. Conclusion Transcatheter stenting of the feeding ductus arteriosus re‐established pulmonary artery flow and growth. Successful surgical repair was achieved, and normal perfusion and complete function of the ipsilateral lung were regained.